Distribution of symptomatic cerebral vasospasm following subarachnoid hemorrhage assessed using cone-beam CT angiography. (5th November 2021) - Simonato, Davide; Borchert, Robin Jacob; Vallee, Fabrice; Joachim, Jona; Civelli, Vittorio; Cancian, Luca; Houdart, Emmanuel; Labeyrie, Marc-Antoine
Abstract : Background and purpose: Cone-beam CT angiography (CB-CTA) provides a three-dimensional spatial resolution which is, so far, unmatched in clinical practice compared with other conventional techniques such as two-dimensional digital subtracted angiography. We aimed to assess the distribution of symptomatic cerebral vasospasm following aneurysmal subarachnoid hemorrhage (aSAH) using CB-CTA. Methods: 30 consecutive patients with aSAH undergoing vasospasm percutaneous balloon angioplasty (PBA) were recruited and underwent CB-CTA in this single-center prospective cohort series. Intracranial arteries were systematically analyzed by two independent observers from the large trunks to the distal cortical branches and perforators using a high-resolution reconstruction protocol. Intermediate and severe cerebral vasospasm was defined as 30–50% and >50% narrowing in the diameter of the vessel, respectively. Results: 35 arterial cervical artery territories were analyzed, of which 80% were associated with clinical or radiological signs of delayed cerebral ischemia. The median spatial resolution was 150 µm (range 100–250 µm). Intermediate or severe vasospasm was observed in the proximal (86%, 95% CI 74% to 97%), middle (89%, 95% CI 78% to 99%), and distal (60%, 95% CI 44% to 76%) segments of the large trunks, as well as the cortical branches (11%, 95% CI 1% to 22%). No vasospasm was observed in basal ganglia or cortical perforators, or in arteries smaller than 900 µm. Vasospasm was more severe in middle or distal segments compared with proximal segments in 43% (95% CI 26% to 59%) of cases. Conclusions: Our study demonstrated that symptomatic cerebral vasospasm following aSAH did not involve arteries smaller than 900 µm, and frequently predominated in middle or distal segments. These results offer new insights into the potential management options for vasospasm using PBA.